A COMPARATIVE ANALYSIS OF E-COMMERCE SALES STRATEGIES: A CASE STUDY OF PASAR IKAN LAMA TRADITIONAL MARKET - Afifah, Yasmin; Ragilita, Rizkie; Tria, Tria Rizki Maulia; Khatimah, Khusnul; Andriawan, Febri (Academic Solution Publisher, 2024)
In today's digital age, the traditional market sector is facing significant challenges due to the rapid growth of e-commerce. This study aims to compare the sales strategies of traditional market traders, specifically at the Old Fish Market, with those of e-commerce players. By examining the strengths, weaknesses, and challenges of both models, this research seeks to understand how these two approaches can complement each other in the face of increasing market competition. The research employed a qualitative approach, involving interviews with traders, observations, and a review of relevant literature. The findings revealed that while traditional markets offer unique advantages such as personal relationships and product freshness, e-commerce provides wider reach and convenience. To remain competitive, traditional market traders need to adopt a hybrid approach, combining the best of both worlds. This study contributes to the literature on the digital transformation of traditional markets and provides practical insights for policymakers and market stakeholders.